Reduction of N2O by CO via Mans–van Krevelen Mechanism over Phosphotungstic Acid Supported Single-Atom Catalysts: A Density Functional Theory Study - Zhang, Li-Long; Chen, Xue-Mei; Liu, Chun-Guang (Inorganic chemistry, 2019)
In general, reduction of N2O by CO is first performed by N2O decomposition over a catalyst surface to release N2 and form an active oxygen species, and subsequently CO is oxidized by the active oxygen species to produce CO2. However, the strong adsorption behavior of CO on the catalyst surface usually inhibits adsorption and decomposition of N2O, which leads to a low activity or poisoning of catalysts. In the present paper, a Mans–van Krevelen (MvK) mechanism has been probed based on a series of phosphotungstic acid (PTA) supported single-atom catalysts (SACs), M1/PTA (M = Fe, Co, Mn, Rh, Ru, Ir, Os, Pt, and Pd). Although the calculated adsorption energy of CO is exceedingly higher than N2O for our studied systems, the adsorbed CO could react with the surface oxygen atom of the PTA support through the MvK mechanism to form an oxygen vacancy on the PTA surface. N2O acts as an oxygen donor to replenish the PTA support and release N2 in the whole reaction process. This proposed reaction mechanism avoids competitive adsorption and poisoning of the catalyst caused by CO. The calculated adsorption energy, oxygen vacancy formation energy, and the free energy profiles show that the catalytic activity of Pd1/PTA, Rh1/PTA, and Pt1/PTA SACs is quite high, especially for Pt1/PTA and Pd1/PTA systems. Meanwhile, molecular geometry and electronic structure analysis along the favorable reaction pathway indicates that the metal single atom not only plays the role of adsorbing CO and activating surface atoms of the PTA support but also works as an electron transfer media in the whole reaction process. We expect that the present calculated results could provide some clues for the search for appropriate catalyst for reduction of N2O to N2 by CO at low temperature.